2007
DOI: 10.1080/10284150701523168
|View full text |Cite
|
Sign up to set email alerts
|

Can a reward-based behavioural test be used to investigate the effect of protein–energy malnutrition on hippocampal function?

Abstract: Our laboratory is investigating the effects of protein-energy malnutrition (PEM) on cognitive outcome following global ischemia. Here, we investigated whether PEM independently impairs working memory in the T-maze and if the associated food reward reverses PEM. Gerbils were fed 12.5% (control diet) or 2% protein. A loss of body weight (20.1%) in the 2% protein group and decreased food intake and serum albumin concentration compared to controls (17.5% and 18.2%, respectively) indicated that PEM was achieved. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Future studies with Golgi-Cox staining and electrophysiology to examine dendritic morphology and synaptic strength, respectively, will also be needed to reinforce the study results. Our findings are reminiscent of the extensive literature on the adverse effects of perinatal malnutrition on synaptic plasticity in the hippocampal formation [43] , [44] , although some of these studies are limited by flaws in the methodology for the nutritional regimens (reviewed in [45] ).…”
Section: Discussionmentioning
confidence: 69%
“…Future studies with Golgi-Cox staining and electrophysiology to examine dendritic morphology and synaptic strength, respectively, will also be needed to reinforce the study results. Our findings are reminiscent of the extensive literature on the adverse effects of perinatal malnutrition on synaptic plasticity in the hippocampal formation [43] , [44] , although some of these studies are limited by flaws in the methodology for the nutritional regimens (reviewed in [45] ).…”
Section: Discussionmentioning
confidence: 69%
“…Another study on gerbils has reported that the animals had more difficulty learning the win-stay rule than the win-shift rule [ 3 8 ]. In most of these studies, the win-shift task, not the win-stay task, was used to evaluate cognitive impairment via examination of food-searching behavior after ischemia [ 23 30 ]. Further, the passive avoidance test has also been used to evaluate cognitive impairment after ischemia [ 4 29 33 ].…”
Section: Introductionmentioning
confidence: 99%